Production planning and control in the Diki Ceramic home industry - Novemy Triyandari Nugroho; Agus Suyatno; Rahayu Pancaningsih (Institute of Computer Science (IOCS), 2023)
Diki Ceramics is an industry that produces pottery with its address at Pagerjurang RT 02 RW 04, Melikan, Wedi, Klaten, Central Java using the main ingredients of black soil and red soil. Companies often cannot estimate the right amount of production to meet market demand. The company expects that there will be no shortage of products which will result in lost opportunities to sell products, but also does not expect that there will be excess products which will result in increased inventory costs. The method used as the optimal solution to determine the amount of pottery production is the dynamic programming method. Variable production planning decisions are taken based on the activities in the factory, namely production activities and raw material procurement activities. The target to be achieved from this research is to determine the optimal level of production in order to get maximum profit by using the dynamic programming method. The total optimal production cost obtained by dynamic programming is IDR 86,500,000, while the company's total actual production cost in 2021 is IDR 181,501,984. From the comparison results, the research method provides cost savings of Rp. 95,001,984.